The origin and importance of mosque in Islam (2008)
Muslims believe that the basis of human existence in life is worship of the Creator, Allah, and Mosque as the ordained place of worship is strategic in actualising that objective. While the Ka'bah is mentioned in Islamic scriptures as the first house ordained for worship, yet, the use made of mosque in contemporary Muslim society transcends the functions identified with it. Since the sanctification of the Ka’bah as a place of worship by Patriarch Ibrahim, the use made of mosque as a place of worship by Prophet Muhammad has transformed it to a place not only for ecumenical functions but also for social concern. While mosque has undergone stages of transformation in its usage and design, all mosques must be made to face the direction of the Ka’bah in Mecca.